PENDIDIKAN TINGGI KRISTEN DI INDONESIA: Sarjana Pantekosta Berebut Ruang di Indonesia: CHRISTIAN HIGHER EDUCATION IN INDONESIA: Pentecostal graduates fighting for space in Indonesia - Elia Tambunan (Sekolah Tinggi Teologi Satyabhakti, Malang)
Pentecostal studies are too prevalent in terms revivalism, movements, and denominations globally. This paper is different because of the anthropological aspects of Pentecostalism outlines how intellectuals Pantecost defines itself in a variety of social situations in which they live. Through a combined quantitative and qualitative research, the authors found Pantecostal scholars find themselves in the time of torpor to redefine themselves and their strategic position in the social reality. Pantecostal scholars could be seen as a representation of the face of Christian higher education in Indonesia. The time of torpor in Pantecostal scholars start from the process of education in higher education who have feelings too in love with its own identity so that the bad impact on the general principles of a system of community-wide. This paper can be seen as a Pantecostal Church in Indonesia (GPdI) scholar contribution towards Pentecostal studies globally from the anthropologist perspective with the Pantecostal scholar use as the unit of analysis in the study of religion is still rarely used by the religious scholar in Indonesia. === Studi Pentakosta yang ada terlalu lazim dalam hal revivalisme, gerakan-gerakan, dan denominasi secara global. Tulisan ini berbeda karena menguraikan Pentakostalisme dari aspek antropologis bagaimana kaum intelektual Pantekosta mendefinisikan dirinya sendiri dalam berbagai situasi sosial di mana mereka hidup. Lewat penelitian gabungan kuantitatif dan kualitatif, penulis menemukan kelambanan sarjana Pantekosta untuk mendefinisikan ulang diri dan posisi strategis mereka dalam realitas sosial yang sangat luas. Sarjana Pantekosta bisa dilihat sebagai representasi wajah pendidikan tinggi Kristen di Indonesia. Kelambanan itu bermula dari proses pendidikan sarjana di lembaga pendidikan tinggi yang memiliki perasaan terlalu cinta kepada identitas sendiri sehingga berdampak buruk pada prinsip-prinsip umum dari satu sistem masyarakat luas. Tulisan ini bisa dilihat sebagai satu kontribusi Gereja Pantekosta di Indonesia terhadap studi Pentakosta secara global dari sisi antropologis dengan menggunakan sarjana Pantekosta sebagai unit analisis dalam studi agama yang masih jarang dipakai sarjana keagamaan di Indonesia.